Risks and opportunities of establishing a European Monetary Fund based on the European Stability Mechanism - Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2017)
The French presidential elections could lead to more fiscal integration in the euro area. The proposal to establish a European Monetary Fund (EMF) based on the European Stability Mechanism (ESM), which would probably be possible without treaty changes, is evaluated in this paper. Potential EMF instruments are divided into two categories. Firstly, to strengthen the rules-based EMU framework the EMF could not only replace the IMF in crisis programmes, but could also monitor the implemen-tation of EMU rules by the EU Commission. However, problematic implementation issues could arise. Moreover, in order to strengthen financial market discipline, the EMF could become both platform and agent for an effective and reliable sovereign debt restructuring mechanism. However, as this idea will meet with considerable political resistance, it could probably be only a part of a larger political compromise. [...]
Keywords: 330